Examining the Impact of Systemic Tensions on Agency and Identity: The Multiple Positions of Reggie in Production-Centered, Technology-Mediated Activity. Issue 2 (3rd April 2021) - Wilson, Nicholas C.
Abstract: This paper presents two examples of production-centered, technology-mediated activities in a one-to-one laptop classroom, and examines how those activities supported vastly divergent forms of student agency and participation. As schools turn to large-scale technology programs, such as one-to-one initiatives, to overcome persistent educational and social inequalities, growing concerns over a widening participation gap in production-centered activities are calling on educators to forge new technology-mediated learning experiences that bridge students' lived experiences and interests with educational content. The findings of this study, however, show that production-centered, technology-mediated activities may inadvertently stifle engagement and agency if they do not leverage students' personal funds of knowledge in the co-construction of new educational practices or participation structures. Analyzed through the lenses of cultural historical activity theory and identities-in-practice, the paper follows Reggie, a high school senior and native Haitian who chronically disengaged from classroom activities, despite an interest and significant background knowledge in digital media production. Discussion centers on the ways in which classroom activities afforded opportunities for Reggie to leverage this knowledge, leading, in one case, to rule-based tensions that ended in the elimination of projects and student autonomy, and in the other, to a remarkable transformation of Reggie's identity-in-practice, in which he helped to co-construct a new division of labor for achieving the object of activity. The paper ends with an argument for the consideration of coordinated changes to multiple elements of activity, and their implications on social practice as essential components of technology program design, and of framing participation-based digital education inequities.